Adaptation of the Authentic Followership Scale into Indonesian: A Validity Study - Utomo, Triyo; Handoyo, Seger; Fajrianthi, Fajrianthi (Universitas Ahmad Dahlan, 2025)
Authentic followership has been proven to contribute to increasing the effectiveness of leadership and organizational performance. Authentic followership has four-dimensional structures, namely self-awareness, balanced processing, relational transparency, and internalized moral perspective. Based on previous studies, the only measuring instrument that is comprehensive enough to reveal the construct of authentic followership is the authentic followership scale by Leroy et al. In this regard, the purpose of this study is to adapt the authentic followership scale into the Indonesian language and test its validity. To determine the content and construct validity of the measuring instrument, this study involved 531 participants (M age = 42.31, SD = 9.76; 58% female and 42% male). The results of the Confirmatory Factor Analysis (CFA) proved that the four-factor measurement model (16 items) fit the empirical data obtained. This finding indicates that the Indonesian adaptation of the authentic followership scale has internal validity and construct validity as a measuring instrument. This study has limitations related to participants who only involved members of public organizations from East Java. Therefore, further research should involve members of public organizations from various organizations throughout the province. The originality of this study is the only adaptation process of the authentic followership scale in the Indonesian language that has ever existed.